Clinical Cases of Wernicke Encephalopathy - G. R. Ramazanov; E. A. Kovaleva; V. N. Stepanov; H. V. Korigova; E. V. Shevchenko; Y. V. Zabrodskaya; S. S. Petrikov (Неотложная медицинская помощь, 2020)
Abstract This article will discuss the causes of Wernicke encephalopathy, diagnosis, treatment and clinical examples of this disease.